Pengaruh Harga dan Kualitas Produk Terhadap Kepuasan Konsumen Minyak Goreng Bimoli - Nurhidayanti Nurhidayanti; Intisari Haryanti; Sri Ernawati (Indonesian Journal of Multidisciplinary on Social and Technology, 2024)
Based on the results of observations by researchers from several consumens who buy and use bimoli cooking oil in the city of bima, there are bulk cooking oils that are competitors to bimoli, apart from that the price is less affordable and the packaging is less attractive compared to the packaging other cooking olis. This research as conducted ith the aim of examining the influence of price and product quality on consumer satisfaction of bimoli cooking oil in bima city. This research uses descriptive research methods. The research instrument used is questionnaire data using a likert scale. The population of this research is unknown population, namely the people of bima city how buy and use an unknown number of bimoli. The sample used was 96 respondents with a purposive sampling technique. Sampling, the research location was carried out in bima city, west nusa tenggara barat. The data collaction techniques used ere observation, questionnaries and literature sudy. The date analysis techniques used were validity tests, reliability test, classical assumption test, namely, normality tests, multicollinearitytest, heteroscedascity tests,autocorrelation test, multiple linear regression, coefficient and multiple correlation, t test and f test. The results of the research show that there is not partially any influence of price on consumer satisfaction of bimoli cooking oil in the city of bima, partially there is an influence of product quality on cooking oil coustumer decisions bimoli in the city of bima, simultaneously the price and quality of the product influence the decisions of consumers of cooking oil in the city of bima.